Impact of Habitual Exercise on Locomotive Function of Middle-aged and Elderly Volunteers: A Longitudinal Study - Yamada, Tomohiro (Prog Rehabil Med, 2021)
OBJECTIVES: This longitudinal study aimed to evaluate the effect of acquisition of an exercise habit on locomotive dysfunction (LD). METHODS: The subjects were 121 male and 196 female volunteers aged more than 50 years who attended health checkups in Toei, central Japan, in 2012 and 2014. We divided the subjects into three groups: an acquiring exercise group (Ac-Ex) composed of those who acquired an exercise habit between 2012 and 2014, a non-exercise group (Non-Ex) who did not acquire an exercise habit, and an exercise group (Ex) who already had an exercise habit in 2012. We compared the 25-question Geriatric Locomotive Function Scale (GLFS-25) score among the three groups. RESULTS: In men in the Ac-Ex group, the GLFS-25 score improved significantly between 2012 and 2014 (P=0.046), and sub-analysis of the GLFS-25 responses showed that fundamental and instrumental activities of daily living (ADL) improved significantly. In women in the Ac-Ex group, the prevalence of radiologically diagnosed knee osteoarthritis was significantly higher (P=0.027) than that for the other two groups, and there was no significant improvement in GLFS-25 score over the 2-year period. CONCLUSIONS: The acquisition of an exercise habit had a positive effect on the locomotive function in men. Orthopedic surgeons must enlighten people on the need for a continuous exercise habit.